The close relationship between sudden loss of smell and COVID-19 - Joffily,Lucia (2020)
Abstract Introduction: The real number of COVID-19 cases may be underestimated since several countries have difficulty offering laboratory tests for all the population. Therefore, finding a symptom with a high predictive value would help in diagnostic and isolation strategies. Objective: To correlate the sudden loss of the sense of smell in the context of the COVID-19 pandemic with results of diagnostic tests for COVID-19. Methods: This is a cross-sectional observational study. An online questionnaire was digitally addressed to 725 outpatients in Brazil who reported partial or total sudden loss of the sense of smell from March to April 2020. Results: Total or partial sudden loss of the sense of smell showed high positive predictive value for COVID-19 diagnosis, during the COVID-19 pandemic in Brazil (88.8%). There were no differences between groups tested positive and negative in regard to demographic and clinical characteristics such as presence of allergy, rhinitis, neither to olfactory recovery time. Conclusion: The identification of sudden loss of the sense of smell during COVID-19 pandemic may serve as a sentinel symptom and may be a warning to establish measures to prevent the transmission of the disease.